Anti-Thyroid Peroxidase/Anti-Thyroglobulin Antibody-Related Neurologic Disorder Responsive to Steroids Presenting with Pure Acute Onset Chorea. (8th July 2020) - Ghosh, Ritwik; Chatterjee, Subhankar; Dubey, Souvik; Pandit, Alak; Ray, Biman Kanti; Benito-León, Julián
Background: Pure acute onset chorea without encephalopathy has rarely been reported in anti-thyroid peroxidase (anti-TPO)/anti-thyroglobulin (anti-TG) antibody-related neurologic disorders responsive to steroids (ATANDS). Case report: We report a 16-year-old female who presented with acute chorea without encephalopathy. Anti-TPO antibodies were found to be strongly positive (>1200 IU/ml) along with anti-thyroglobulin and anti-thyroid stimulating hormone receptor antibodies. After pulse intravenous methylprednisolone therapy (1 g/day for five consecutive days), all the movements seized, and she was discharged with oral prednisolone 30 mg/day with gradual tapering over next three months. After one year of follow-up, she is stable, drug-free, and never had any other problems. Discussion: Anti-thyroid antibodies testing should be included in routine/conventional panel that is done for elucidating causes of chorea as ATANDS can be easily missed and is treatable with widely available, relatively low-cost drugs like steroids with a promising outcome.